Active Obstacle Avoidance of Multi-Rotor UAV Swarm Based on Stress Matrix Formation Method - Zhenyue Qiu; Lei Zhang; Yuan Chi; Zequn Li (Mathematics)
Aiming at the formation problem of the multi-rotor UAV swarm, this paper adopts a multi-rotor UAV swarm formation control method based on a stress matrix to ensure the stability of multi-rotor UAV swarm formation. On the basis of achieving the target formation through a stress matrix, the formation of a multi-rotor UAV swarm can be rotated, scaled, and sheared. When the obstacles are known, the multi-rotor UAV swarm can pass through the obstacle environment smoothly through rotation, scaling, and shearing transformations. However, this transformation cannot cope with the situation where the obstacles are known. This paper proposes an active obstacle avoidance function for multi-rotor UAV swarm formation based on a stress matrix. Through the detection capability of the UAV itself, the obstacle avoidance function is realized autonomously after the UAV detects an unknown obstacle. Due to the effect of a stress matrix, when the navigator performs the active obstacle avoidance function, the formation of the multi-rotor UAV swarm will be destroyed. This paper designs a virtual UAV and only retains the UAV that controls the flight trajectory of the multi-rotor UAV swarm as the only real UAV to ensure that the UAV swarm formation is not destroyed. This paper proves the stability of the multi-rotor UAV swarm formation through simulation experiments, and the multi-rotor UAV swarm can pass through the obstacle environment smoothly when facing known obstacles and unknown obstacles.